Pelatihan dan Pembuatan Hidroponik Menggunajan Metode Wick System dan Deep Flow Technique - Sigmayuriza Devinnandy Trisnanda; Agam Prasitiyo; Ahmad Choirun Nidak; Amir Ahnaf Hibatulloh; Hendra Junianto; Dia Puspitasari (ABDIMAS TERAPAN : Jurnal Pengabdian Kepada Masyarakat Terapan, 2025)
The development of suburban areas and the rapid conversion of agricultural land into settlements in Jimbaran Wetan Village, Wonoayu District, Sidoarjo Regency, have given rise to new challenges in meeting the community's food needs. One solution offered is the application of a hydroponic system as a form of modern agriculture that is efficient and environmentally friendly. This training activity aims to improve community knowledge and skills in managing household-scale hydroponic systems. The training method is carried out through theoretical counseling, demonstrations, and direct practice in making simple wick and DFT hydroponic systems. The results of the activity showed a significant increase in the participants' understanding, as well as their ability to assemble and manage hydroponic systems independently. In addition, this training succeeded in fostering residents' interest in utilizing their yards as a medium for cultivating productive plants. This activity is expected to be the first step in developing community-based modern agriculture in rural areas.